Intercultural communication competence conceptualization and its development in cultural contexts and interactions - Dai, Xiaodong; Chen, Guo-Ming (Cambridge Scholars Publishing, 2014)
Intercultural communication competence is an indispensable ability for people to interact appropriately and effectively across nations and regions in the globalized world. Competent intercultural communication enables people to reach mutual understanding as well as reciprocal relationships. In recent decades, considerable progress has been made in the research of intercultural communication competence. However, due to its complexity, many problems remain unanswered and need to be addressed. ...